Bactericidal activity of ciprofloxacin compared with that of cefotaxime in normal volunteers. - Standiford, H C (1987)
We compared ciprofloxacin (200 mg) with cefotaxime (2 g) when each was administered intravenously over a 30-min period to six volunteers in a crossover manner 1 week apart. To integrate the pharmacologic and microbiologic activity, inhibitory and bactericidal activities in serum were obtained for both antibiotics 1 and 6 h after administration against 10 strains of Escherichia coli, 10 strains of Klebsiella pneumoniae, 15 strains of Pseudomonas aeruginosa, and 10 strains each of methicillin-susceptible and -resistant Staphylococcus aureus. Geometric mean bactericidal titers for E. coli 1 h after the infusion were 1:60 for ciprofloxacin and 1:252 for cefotaxime, and for K. pneumoniae they were 1:20 and 1:256, respectively. However, geometric mean titers were poor for both antibiotics against methicillin-susceptible S. aureus (less than 1:2 for ciprofloxacin versus 1:5 for cefotaxime) and methicillin-resistant S. aureus (less than 1:2 for both antibiotics), as well as against P. aeruginosa (1:3 for ciprofloxacin versus 1:2 for cefotaxime). These data suggest that ciprofloxacin may be useful for the treatment of serious infections caused by E. coli and K. pneumoniae. However, caution is suggested when this dose of ciprofloxacin is used in situations in which septicemia is caused by P. aeruginosa or S. aureus and originates outside the urinary tract.